Credit Loan Application Procedure via BRImo Application - Novianti, Nadia Seely; Kartikasari, Hanum (Journal of Management and Administration Provision, 2025)
The process of applying for a credit loan online is very easy, fast, efficient, and does not require collateral and a survey process. One of the digital services that supports this convenience is the BRImo Application from Bank Rakyat Indonesia (BRI). The purpose of this study is to systematically describe the procedure for applying for a credit loan through the BRImo application. The method used is descriptive qualitative with a field study approach through direct observation and interviews with related staff. The results of the study show that the procedure for applying for a loan through BRImo includes several main stages, namely logging into the application, selecting the loan menu, completing personal data and business data, and waiting for automatic approval without requiring a field survey. This procedure has been proven to reduce time and costs and increase the efficiency of banking services. However, there are several technical obstacles found, such as network disruptions, data inconsistencies, and limited digital literacy of customers. By understanding the procedures and obstacles, it is hoped that digital banking services such as BRImo can continue to be improved to support financial inclusion in Indonesia.